Influence of modified mesoporous silica SBA‐15 on the flammability of intumescent high‐density polyethylene. (7th April 2016) - Matar, M.; Azambre, B.; Cochez, M.; Vahabi, H.; Fradet, F.
Abstract : This work aims to investigate the fire retardant properties of a novel type of high‐density polyethylene composites. Our intumescent system consists in using classical flame retardants such as ammonium polyphosphate, pentaerythritol in combination with porous mesostructured silica (SBA‐15) fillers. Prior to use, SBA‐15 was chemically modified using different organic and inorganic grafts in order to obtain some specific properties, such as an improved compatibility with the polymer, or different types of surface acidity in order to increase charring reactions. Limiting oxygen index, UL‐94, pyrolysis flow combustion calorimetry and thermogravimetric analysis were used to assess the burning behavior and thermal stability, respectively, of the processed composites. By keeping the total amount of additives always equal to 25 wt%, the better flammability characteristics were in general obtained at low SBA‐15 loadings (<2 wt%). X‐ray diffraction and Fourier transform infrared spectroscopy analyses of the residues showed that the formation of a barrier mainly constituted by crystalline silicon phosphates is probably a key to enhance the fire properties. Further slight improvements brought by the surface modification of SBA‐15 nanofillers are discussed according to type of incorporated particles. Copyright © 2016 John Wiley & Sons, Ltd.